Neuroprotective potential of Piroxicam in cerebral ischemia: An in silico evaluation of the hypothesis to explore its therapeutic efficacy by inhibition of aquaporin-4 and acid sensing ion channel1a - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R. (My University, 2025)
Cerebral stroke is caused by acute interruption of the brain arterial blood supply and is one of the major health problems with no effective treatments so far apart from the thrombolytic recombinant tissue plasminogen activator (rt-PA), which must be administered within 3. h of stroke onset. This emerges it as the third leading cause of mortality worldwide. Acidosis and brain edema are the prominent metabolic features of ischemic brain. The combined inhibition of aquaporin-4 (AQP4) and ASIC1a channels may offers a new neuroprotective approach in cerebral stroke management. Moreover, the combined inhibition of AQP4 and ASIC1a with NSAID remains unknown against neuroprotection in animal models of cerebral ischemia. NSAIDs are believed to act as a pharmacological molecule that reported to have an antioxidant and anti-inflammatory properties. Therefore, the target of the present in silico study was to determine the neuroprotective efficacy of Piroxicam, a NSAID in animal model of cerebral ischemia/reperfusion (I/R) injury and efforts were made to analyze its inhibitory effects on aquaporin-4 activation and ASIC1a channels mediated downstream survival/damage mechanisms. Thus we hypothesized that Piroxicam, a NSAID can act as a neuroprotective agent in animal model of cerebral ischemia/reperfusion (I/R) injury due to its inhibitory effects on aquaporin-4 channel and ASIC1a channels. It is indeed vital that we do not give up the fight to develop compounds to treat stroke despite the many years of setbacks. One of the mottos of our proposed hypothesis is to find out a successful modality of effective substantial treatment of brain stroke with other anti stroke therapeutics available till date. © 2012 Elsevier Ltd.